Localized eCommerce Development Using User-Centered Waterfall for Better SME Trade Processes - Najla Ramadina Sulistyowati; Deki Satria; Qilbaaini Effendi Muftikhali (Journal of Information System Research (JOSH), 2025)
e-Marketplaces are one of the ways for SMEs to reach their market. Many marketplaces, such as Tokopedia or Shopee, provide marketplaces for SMEs. But, this kind of marketplace has a huge admin fee, which could reduce the SMEs' profit. A localized marketplace is needed to provide a way for SMEs to reach their intended market. POG is one marketplace that allows SMEs to reach their market using WhatsApp. But this tool is not suitable for trading goods. A localized website-based market is more appropriate. The combination of waterfall methodology and user-centered approach is used to develop the marketplaces. Waterfall is a methodology usually used to develop software that works like a waterfall from planning to implementation. User-centered design is a development process that heavily includes the user in planning to capture what the user needs. Using this methodology, many requirements were left out, especially the detailed requirements, such as constraints on the input. Blackbox testing as a test methodology is also inadequate to use if the test case is not thorough enough to test all of the system's possibilities. Therefore, using an iterative methodology is more suitable for marketplace development. Because all of the inadequate requirements and tests can be detected more easily and earlier. Therefore, it increases the development success rates. This research results in a localized e-commerce website that the POG can use to enhance its process.